Dunkirk - Nolan, Christopher 1970- (Faber & Faber, 2017)
Christopher Nolan's previous films have reflected the uncertainties of the twentieth-first century. With Dunkirk, Nolan has gone back into the past and brought to life one of the momentous events of the twentieth-century - the evacuation of British troops from Dunkirk, telling the tale by land, sea, and sky. Dunkirk opens as hundreds of thousands of British and Allied troops are surrounded by enemy forces. Trapped on the beach with their backs to the sea, they face an impossible situation as the enemy closes in. The film features a prestigious cast, including Kenneth Branagh, Cillian Murphy, and newcomer Fionn Whitehead, with Mark Rylance and Tom Hardy.The screenplay is accompanied by a conversation about the film between Christopher Nolan and Jonathan Nolan,as well as selected storyboards
Keywords: Dunkirk -- Film -- 2017; Dunkirk (Motion picture : 2017); Dunkirk, Battle of, Dunkerque, France, 1940; Screenplays; Motion picture plays; Drehbuch